Memaknai Teguran Bildad dalam Ayub 8 Sebagai Refleksi Terhadap Keadilan Allah dalam Kehidupan Orang Percaya - Nidia Anggraini; DICKY DOMINGGUS (Sekolah Tinggi Teologi Internasional Harvest Tangerang, 2022)
Job is a picture of a godly man who experienced suffering. In his suffering, Job also received accusations from his friends that he had sinned so that God gave him suffering. Bildad was one of his friends who gave a strong rebuke to Job to seek and seek God's mercy. In achieving the objectives, this research uses qualitative research methods. The approach used is historical grammatical. Bildad's rebuke is based on the understanding of the ancient tradition that Suffering and sin are inseparable. Likewise with the other two friends, Eliphaz and Zophar, who saw Job's suffering more as a consequence of the sins he had committed. Unlike Job, who has the concept of God as a creative person with his works and is fully sovereign in human life. This difference is the basis of the long dialogue between Job and his friends.